2018
DOI: 10.1039/c8lc00686e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on the plasma vesicular proteome: a methodological study comparing acoustic trapping and centrifugation

Abstract: a Extracellular vesicles (EVs) are a heterogeneous group of actively released vesicles originating from a wide range of cell types. Characterization of these EVs and their proteomes in the human plasma provides a novel approach in clinical diagnostics, as they reflect physiological and pathological states. However, EV isolation is technically challenging with the current methods having several disadvantages, requiring large sample volumes, and resulting in loss of sample and EV integrity. Here, we use an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Yet, we did not find evidence that muscle cells or hepatic cells contribute to the ExerV pool in our exercise setting. In a recent study using acoustic trapping, ExerVs have been studied 1 h after exercise [53]. Similar to us, the group reported the release of protein cargo of the respective ExerVs that mostly reflect proteins known to be released or expressed by either blood cells, or the endothelium.…”
Section: Discussionmentioning
confidence: 80%
“…Yet, we did not find evidence that muscle cells or hepatic cells contribute to the ExerV pool in our exercise setting. In a recent study using acoustic trapping, ExerVs have been studied 1 h after exercise [53]. Similar to us, the group reported the release of protein cargo of the respective ExerVs that mostly reflect proteins known to be released or expressed by either blood cells, or the endothelium.…”
Section: Discussionmentioning
confidence: 80%
“…We have previously shown that the proteomic composition of EVs analyzed with mass spectrometry is highly similar comparing acoustic seed trapping and high-speed centrifugation 26 but wanted to confirm that there was no impact of EV isolation technique on the results of the proximity extension assay. To this end, we re-analyzed a previously published data set 27 comprising a total of 30 acoustically trapped and 30 centrifuged EV samples from 10 healthy donors assayed with the Olink CVD II PEA Panel. 59 and 55 proteins were detected (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes, an important group of extracellular vehicles (EVs), are membrane‐contained vesicles that carry protein, nucleic acid, and lipid cargoes released from a wide range of cell types . According to their size, membrane composition and content, exosomes are defined as a homogenous population of endogenous vesicles with a diameter of 30–200 nm, which are derived from inward budding of the multivesicular body membrane and secreted into the outside of the cells upon fusion of multivesicular body and plasma membrane .…”
Section: The Exosome Perspectivementioning
confidence: 99%